Workplace Disability: Whose Wellbeing Does It Affect? - Getinet Astatike Haile (Institute for the Study of Labor (IZA), 2016)
The paper examines the link between workplace disability (WD) and job satisfaction (JS) in Britain using linked data from WESR2011. The results obtained indicate workplaces with respondents with disabilities report lower JS vis-à-vis workplaces without such respondents in the private sector. Within private sector workplaces with mixed respondents, the JS of respondents without disabilities declines with the percentage of respondents with disabilities. Also, workplace disability policies and practices are positively (negatively) associated with the JS of respondents with (without) disabilities in the sector. The sector may have to re-examine its dealings with issues of workplace disability.
Keywords: J14; J82; J7; I31; 330; workplace disability; job satisfaction; linked data; Britain